Associations among body composition, inflammatory profile and disease extent in ulcerative colitis patients - Urbano, Ana Paula Signori [UNESP]; Sassaki, Ligia Yukie [UNESP]; De Souza Dorna, Mariana [UNESP]; Presti, Paula Torres [UNESP]; De Barros Leite Carvalhaes, Maria Antonieta [UNESP]; Martini, Ligia Araújo; Ferreira, Ana Lucia Anjos [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: The aim of our study was to assess body composition status and its association with inflammatory profile and extent of intestinal damage in ulcerative colitis patients during clinical remission. Method: This is a cross-sectional study in which body composition data (phase angle [PhA], fat mass [FM], triceps skin fold thickness [TSFt], mid-arm circumference [MAC], mid-arm muscle circumference [MAMC], adductor pollicis muscle thickness [APMt]), inflammatory profile (C-reactive protein [CRP], α1-acid glycoprotein, erythrocyte sedimentation rate [ESR]) and disease extent were recorded. Results: The mean age of the 59 patients was 48.1 years; 53.3% were women. Most patients were in clinical remission (94.9%) and 3.4% was malnourished according to body mass index. PhA was inversely correlated with inflammatory markers such as CRP (R=-0.59; p<0.001) and ESR (R=-0.46; p<0.001) and directly correlated with lean mass: MAMC (R=0.31; p=0.01) and APMt (R=0.47; p<0.001). Lean mass was inversely correlated with non-specific inflammation marker (APMt vs. ESR) and directly correlated with hemoglobin values (MAMC vs. hemoglobin). Logistic regression analysis revealed that body cell mass was associated with disease extent (OR 0.92; 95CI 0.87-0.97; p<0.01). Conclusion: PhA was inversely correlated with inflammatory markers and directly correlated with lean mass. Acute inflammatory markers were correlated with disease extent. Body cell mass was associated with disease extent.
Keywords: Biomarkers; Body composition; C-reactive protein; Severity of illness index; Ulcerative colitis